EXPLORING FACTORS BEHIND THE USE OF WRITING TOOL ASSISTANT: A TENDENCY AMONG EFL LEARNERS - Anditasari, Amira Wahyu; Sitompul, Siti Kholija (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
This present study aimed at identifying the students' tendency to use Grammarly to check and improve their writing texts. Various factors contributed to the use of Grammarly; thus, this study emerges to explore the English Department students' responses toward the use of Grammarly. The responses were explored through a descriptive qualitative study using a semi-structured interview involving seven students from the English Department in a state university located in Malang who were Grammarly users for approximately two semesters. The interview was held online through the Zoom application to easily access the students' locations. The interview results were qualitatively analyzed using a thematic design consisting of transcribing, coding, and categorizing the data. The results were categorized into three main aspects of consideration: (1) using Grammarly, (2) selecting Grammarly features to be checked, (3) accepting Grammarly's feedback. Referring to the first aspect, the students affirmed that they checked their writing products to check grammar correctness and vocabulary appropriateness. Moreover, lack of confidence influences the students to use Grammarly. The second aspect related to Grammarly features turned out that correctness and clarity aspects were the most features checked by the students to ensure the appropriateness of sentence structures, wording, clarity of sentences, and punctuation. The last aspect refers to how the students deal with Grammarly feedback. The students contended that they never entirely accepted the detections from Grammarly because sometimes it contained inappropriate detection and irrelevant feedback. Therefore, this study has a significant contribution to diminishing the dependency of students on using Grammarly as a way to improve writing skills and increase writing confidence